Analisis Faktor Risiko TB paru Anak yang Tinggal Serumah dengan Penderita TB paru Dewasa - Yumi Abimulyani; Yuliana Yacinta Kainde; Tri Novianty Mansyur; Neny San Agustina Siregar (Journal of Pharmaceutical and Health Research, 2023)
Pulmonary tuberculosis (TB) is still a major public health problem in Indonesia. Based on the Household Health Survey (SKRT) results tuberculosis is the number one respiratory disease and infectious disease. Tuberculosis in children causes growth disorders and even death. If pulmonary tuberculosis in a child is not treated immediately, it can quickly develop into parenchymal or tubercular pneumonia, milliary tuberculosis, bone tuberculosis (scrofuloderma), joint tuberculosis, abdominal tuberculosis, and even meningitis. This study used a case-control design with analytical observation. Children who were exposed to and lived in the same household with adult pulmonary tuberculosis patients as many as 90 adults participated in the study. The case sample consisted of children aged 0-15 years who were diagnosed with Pulmonary TB by doctors at the Wania Health Center, Mimika Regency. The case sample size was 30 respondents and the control sample was 30 respondents. The free variables in this study were parental knowledge, BCG vaccination history, child nutritional status, occupancy density, the behavior of TB sufferers at home, and length of contact. Data were analyzed using univariate analysis, bivariate analysis, and multivariate analysis (multiple logistic regression). The results of the study analysis showed that the factors that influence the incidence of tuberculosis in children are parental knowledge (p = 0.001), BCG vaccination history (p = 0.001), and the behavior of adult tuberculosis sufferers in the household (p = 0.000) The conclusion of the study was that the behavior of adult pulmonary tuberculosis patients who lived in the same house with children was most influential in the transmission of pulmonary tuberculosis in children who lived in the same household as adult pulmonary tuberculosis patients at the Health Centre of Wania, Mimika District.